KEBIJAKAN PENDIDIKAN SEPANJANG HAYAT DI INDONESIA: TINJAUAN TERHADAP REGULASI DAN IMPLEMENTASI DALAM SISTEM PENDIDIKAN NASIONAL - Faizah, Usrotul; Amelia Putri, Rizka; Putra Sasmitla, Muhamad Azmi; Qomar Arifin, Nurul; Kamilia, Nadya; Khobir, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Lifelong learning is an educational concept that views learning as a continuous process conducted through formal, non-formal, and informal pathways. This study aims to analyze the concept, regulatory foundation, implementation, and challenges of lifelong learning in Indonesia’s national education system. The research employed a qualitative approach using a literature review method through the analysis of national regulations, UNESCO reports, scientific journal articles, and supporting literature. The findings indicate that Indonesia has recognized the principle of lifelong learning through Law Number 20 of 2003 concerning the National Education System, Law Number 13 of 2003 concerning Employment, and the National Long-Term Development Plan 2025–2045. Its implementation is carried out through the integration of formal, non-formal, and informal education pathways. However, several challenges remain, including the absence of comprehensive regulations, unequal digital access, weak inter-agency coordination, limited recognition of Recognition of Prior Learning (RPL), and low public learning culture. Therefore, strengthening regulations, improving digital infrastructure, and fostering a sustainable learning culture are necessary to support the realization of Golden Indonesia 2045.